A study of propagation of cosh-squared-Gaussian beam through fractional Fourier transform systems - Hashemi, Somaye Sadat; Sabouri, Saeed Ghavami; Soltanolkotabi, Mahmood (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
In this paper, we consider properties of cosh-squared-Gaussian beam passing through ideal and apertured fractional Fourier transforms (FRFT) systems. We use Collins integral formula and the fact that a hard aperture function can be expanded into a finite sum of complex Gaussian functions. These studies indicate that the normalized intensity distributions with FRFT order are periodic. The variation period is 2 and is independent of the impact of aperture.
Optica Applicata, Vol. 41, 2011, Nr 4, s. 897-909
Keywords: optyka; cosh-squared-Gaussian; fractional Fourier transforms (FRFT)